Crop response in the Western Cape of South Africa to liming soil under no-tillage and following once-off tillage in a no-tillage regime - Liebenberg, Adriaan (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.